Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/1067828x.2016.1139481
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Adolescents in Foster Care and Their Peers in High School: A Study of Substance Use Behaviors and Attitudes

Abstract: While adolescents in foster care are known to be more at risk for substance abuse, existing studies have significant limitations in their methodology, making it challenging to gauge the extent of current use of drugs, tobacco, and alcohol compared with their same-age peers not in care. This article examined data collected from adolescents currently in foster care alongside their same-aged peers within the same high schools in California, in order to learn more about existing rates of and attitudes toward subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Foster youth were previously found to exhibit high rates of cigarette smoking, putting them at risk for adverse health consequences later in life (Braciszewski & Colby, 2015; Siegel et al, 2016). In the present study, slightly over 40% identified as lifetime smokers, while about 17% identified as current (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Foster youth were previously found to exhibit high rates of cigarette smoking, putting them at risk for adverse health consequences later in life (Braciszewski & Colby, 2015; Siegel et al, 2016). In the present study, slightly over 40% identified as lifetime smokers, while about 17% identified as current (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, while smoking rates for the general population youth declined substantially in recent years (Johnston et al, 2015), smoking rates for foster youth appear to remain relatively stable. In a sample of foster youth from California collected in 2012, 49% identified as lifetime smokers and 25% identified as current smokers (Siegel et al, 2016). In a sample of foster youth from Connecticut collected in 2015, rates of lifetime smoking were 45%, while rates of current smoking were 18% (Zhan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations